The Role of Guidance and Counseling Teachers in Addressing Pornography Issues among Students - Tarigan, Devi Eka Yulita br; Fadilah, Risydah; Situmorang, Khairunnisa (Altruistik : Jurnal Konseling dan Psikologi Pendidikan, 2023)
The phenomenon of pornography exposure among junior and senior high school students has become an increasingly serious concern in the educational context. This study aims to examine the role of guidance and counseling (BK) teachers in addressing and mitigating pornography-related problems in schools. A quantitative descriptive approach was employed in this research. The study involved five guidance and counseling teachers selected purposively from various educational levels in Medan City, including junior high school (SMP), Islamic junior high school (MTs), senior high school (SMA), Islamic senior high school (MA), and vocational high school (SMK). The findings indicate that BK teachers employ diverse counseling techniques, with individual counseling being the most commonly used method. The preventive and remedial efforts undertaken by BK teachers include conducting psychoeducational programs, engaging in parent-teacher collaboration, and establishing partnerships with relevant stakeholders. However, the study also highlights several challenges, particularly the lack of parental supervision and cooperation, which hinders the effectiveness of counseling interventions. These results emphasize the need for strengthening family-school collaboration and developing comprehensive strategies for preventing pornography exposure among adolescents in educational settings.